Asphalt particles and methods of making same, asphalt-based oxidized particles, hard carbon materials and applications, activated carbon materials and applications
Patent Information
- Application Number
- CN202510576005.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-05-06
AI Technical Summary
[0006]本发明的目的是为了克服现有技术中存在的沥青颗粒预氧化稳定化处理高软化点沥青的熔体造粒工艺复杂、熔体造粒后沥青颗粒因预氧化稳定化过程中蓄热引起熔并粘连的问题,提供了一种沥青颗粒及其制备方法、由其制得的沥青基氧化颗粒、以及由沥青基氧化颗粒制得的硬碳材料及应用、活性炭材料及应用
(1)本发明提供的沥青颗粒可有效促进预氧化稳定化过程中沥青颗粒内、外部与空气充分接触,氧化速率更快;同时也促进沥青颗粒内、外部的氧化反应更均匀,避免沥青颗粒在预氧化稳定化过程中因内部蓄热导致的熔并粘连。
Smart Images

Figure CN120607820B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon materials, specifically to a pitch particle and its preparation method, pitch-based oxide particles obtained therefrom, and hard carbon materials and their applications made from pitch-based oxide particles, as well as activated carbon materials and their applications. Background Technology
[0002] Pitch is a common byproduct of the coal and petroleum industries. It is inexpensive and has a high residual carbon content, making it an ideal precursor for preparing carbon materials such as hard carbon or activated carbon. However, in the preparation of hard carbon, without prior pre-oxidation stabilization, pitch-based precursors easily graphitize after high-temperature carbonization, forming soft carbon structures with small interlayer spacing (typically less than 0.37 nm), making it difficult to effectively embed sodium ions and resulting in a significant reduction in sodium storage capacity. Similarly, in the preparation of activated carbon, without prior pre-oxidation stabilization, pitch-based precursors easily melt and agglomerate during carbonization-activation, forming large, dense structures and / or dense skins. This hinders the contact between the pitch-based precursor and the activator, making it difficult to obtain activated carbon with a high specific surface area using pitch-based precursors. Therefore, in the preparation process of the above-mentioned carbon materials, pre-oxidation stabilization is a key step. Its main purpose is to form a stable three-dimensional cross-linked structure on the surface and inside of the pitch-based precursor through oxidation reaction, so as to prevent the pitch-based precursor from graphitizing, melting and sticking together during subsequent carbonization and activation processes, which would affect the application performance of subsequent hard carbon or activated carbon products.
[0003] In the pre-oxidation stabilization process, powdered asphalt is unsuitable as a direct asphalt-based precursor. Firstly, powdered asphalt typically has a particle size of tens of micrometers or even smaller. Under existing pre-oxidation stabilization processes, such as pre-oxidation in a moving bed reactor, powdered asphalt exhibits poor flowability and thermal conductivity, easily leading to localized heat accumulation and melting / agglomeration. Secondly, in rotary kilns, with increased airflow, the phenomenon of powdered asphalt overflowing or leaking from the kiln is significant, and there is also a risk of deflagration. To avoid the poor pre-oxidation processability and dust deflagration risks associated with powdered asphalt, a method of pre-granulating powdered asphalt into asphalt particles is generally adopted. Currently, the main powdered asphalt granulation technology uses melt granulation.
[0004] CN108395899A discloses a melt granulation method for producing water-cooled pitch-based spherical activated carbon. Pitch-based spherical activated carbon particles are prepared by melt granulation. Melted pitch is sprayed into a water-cooled container in the form of droplets. The pitch droplets shrink and cool into spheres in the water due to their own tension, and then undergo subsequent oxidation without melting. When granulating high softening point asphalt, additives such as naphthalene, methylnaphthalene, or dimethylnaphthalene are often added to lower the softening point. After granulation, these additives need to be extracted and removed with a solvent, which means that a naphthalene addition-removal process is necessary. This causes serious environmental pollution due to the volatilization and release of additives during the process, and also negatively affects the stability of the product. At the same time, melt granulation requires the pre-formation of a melt before granulation, making the process complex. Asphalt particles prepared by melt granulation are prone to melting and agglomeration during the pre-oxidation and stabilization process due to heat accumulation. This not only reduces the specific surface area of the subsequent activated carbon material, making the adsorption capacity of the activated carbon material worse, but also causes insufficient pre-oxidation of the asphalt particles due to melting and agglomeration during the pre-oxidation and stabilization process. This makes them prone to graphitization during the subsequent carbonization process, resulting in a significant decrease in the sodium storage capacity of the hard carbon material obtained after carbonization of the asphalt particles.
[0005] Therefore, there is an urgent need to provide a simple process for preparing asphalt particles, while also avoiding the problem of asphalt particles easily melting and sticking together due to heat storage during the pre-oxidation stabilization process. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems in existing technologies, such as the complex melt granulation process for pre-oxidative stabilization of high softening point asphalt, and the melting and agglomeration of asphalt particles caused by heat accumulation during the pre-oxidative stabilization process. This invention provides asphalt particles and their preparation method, asphalt-based oxidized particles obtained therefrom, and hard carbon materials and their applications, as well as activated carbon materials and their applications, all made from asphalt-based oxidized particles. These asphalt particles have sufficient contact with air during the pre-oxidative stabilization process, avoiding melting and agglomeration caused by heat accumulation. Furthermore, the granulation method for these asphalt particles is simple, eliminating the need for a melt process and allowing direct granulation.
[0007] To achieve the above objectives, the first aspect of the present invention provides a method for preparing asphalt particles, the method comprising the following steps: By weight, 100 parts of powdered asphalt are mixed with 5-200 parts of dispersant and 0.1-5 parts of binder and granulated to obtain the asphalt particles.
[0008] A second aspect of the present invention provides asphalt particles prepared by the above-described preparation method, wherein the average diameter of the asphalt particles is 0.5-10 mm; And / or, the bulk density of the asphalt particles is 0.3-0.8 g / cm³. 3 ; And / or, the porosity of the asphalt particles is 5-15%.
[0009] A third aspect of the present invention provides asphalt-based oxidized particles, wherein the asphalt-based oxidized particles are obtained by pre-oxidizing and stabilizing the aforementioned asphalt particles; wherein the pre-oxidizing and stabilizing conditions are: an oxidizing gas atmosphere; starting at room temperature, heating to the pre-oxidizing and stabilizing temperature of 280-350°C at a rate of 0.2-5°C / min, and a residence time of 0.5-6 hours; And / or, the oxygen content of the asphalt-based oxidized particles is 12-35 wt.%.
[0010] The fourth aspect of the present invention provides a hard carbon material, which is obtained by carbonizing the above-mentioned pitch-based oxide particles. The carbonization conditions are as follows: inert gas atmosphere; starting from room temperature, heating to the carbonization temperature of 900-1500°C at a rate of 2-10°C / min, holding at the temperature for 1-3 hours, then cooling to 800-1200°C at a rate of 2-5°C / min, and then naturally cooling to room temperature to obtain the hard carbon material. And / or, the carbon interlayer spacing d of the hard carbon material 002 The value is 0.37-0.41 nm; And / or, the sodium storage capacity of the hard carbon material is 260-400 mAh / g.
[0011] The fifth aspect of this invention provides an application of the above-mentioned hard carbon material in the preparation of battery anode materials.
[0012] The sixth aspect of the present invention provides an activated carbon material, which is obtained by activating the above-mentioned pitch-based oxide particles. The activation conditions are: an inert gas atmosphere; starting from room temperature, heating to the activation temperature of 700-1100°C at a rate of 8-12°C / min, and activating with an activating agent at this temperature for 1-20 hours, followed by natural cooling to room temperature. And / or, the average diameter of the activated carbon material is 0.2-8 mm; And / or, the BET specific surface area of the activated carbon material is 800-2900 m². 2 / g; And / or, the pore volume of the activated carbon material is 0.40-1.36 cm³. 3 / g; And / or, the average pore size of the activated carbon material is 1.83-2.35 nm.
[0013] The seventh aspect of the present invention provides an application of the above-mentioned activated carbon material in the fields of blood purification, industrial wastewater treatment, supercapacitors, silicon-carbon anode carriers, or gas separation.
[0014] The beneficial effects of this invention are: (1) The asphalt particles provided by the present invention can effectively promote the full contact between the inside and outside of the asphalt particles and the air during the pre-oxidation stabilization process, and the oxidation rate is faster; at the same time, it can also promote a more uniform oxidation reaction inside and outside the asphalt particles, and avoid the melting and sticking of asphalt particles due to internal heat storage during the pre-oxidation stabilization process.
[0015] (2) The method for preparing asphalt particles provided by the present invention is simple. Asphalt with a high softening point can be used as raw material. No additives are needed to reduce the softening point of the asphalt, and no melting process is required before granulation. This not only avoids the serious environmental pollution caused by the volatilization of additives during the process, but also ensures the process stability of asphalt particles.
[0016] (3) The asphalt-based oxide particles obtained by the present invention can be carbonized at high temperature to obtain the carbon interlayer spacing d. 002 Hard carbon materials with a nanometer value of 0.37-0.41 nm and a sodium storage capacity of 260-400 mAh / g.
[0017] (4) The asphalt-based oxide particles obtained by this invention, after high-temperature activation, can achieve an average diameter of 0.2-8 mm and a pore volume of 0.40-1.36 cm. 3 / g, average pore size of 1.83-2.35nm, BET specific surface area of 800-2900m² 2 / g of activated carbon material. Attached Figure Description
[0018] Figure 1 This is a photograph of asphalt-based oxidized particles C1 after undergoing a pre-oxidation stabilization process in Example 3 of the present invention.
[0019] Figure 2 This is the XRD pattern of the hard carbon material C2 prepared by the preparation methods of Preparation Example 3, Example 3 and Application Example 3 in this invention.
[0020] Figure 3 This is a nitrogen adsorption isotherm diagram of activated carbon material C3 prepared by the preparation methods of Preparation Example 3, Example 3 and Application Example 9 in this invention. Detailed Implementation
[0021] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0022] Terminology Explanation Section: It is understood that the activator-to-carbon ratio represents the mass of activator (such as water vapor, carbon dioxide, or a mixture of both) that a unit mass of carbonized material comes into contact with during the activation process. In this invention, the activator-to-carbon ratio can be expressed by the following formula: Activator-to-carbon ratio = mass of activator / mass of asphalt-based oxide particles.
[0023] Understandably, the degree of substitution refers to the average number of carboxymethyl or hydroxymethyl substituted hydroxyl groups on each glucosamine unit in a cellulose molecule.
[0024] It is understood that, in this invention, the oxygen content of asphalt-based oxidized particles refers to the mass percentage of oxygen atoms in the asphalt-based oxidized particles that have combined with elements such as carbon and hydrogen to form a stable chemical structure after pre-oxidation and stabilization treatment. This parameter directly reflects the degree of chemical cross-linking and polymerization reaction that occurs between the asphalt particles and oxygen during the pre-oxidation process, and is a key indicator for measuring the sufficiency and uniformity of the pre-oxidation reaction.
[0025] It is understood that the "granulation" of this invention refers to the process by which asphalt powder, with the help of a binder, adheres and agglomerates with each other to form asphalt particles.
[0026] Understandably, the diameter of granulated asphalt particles directly affects the speed and depth of oxygen molecule diffusion from the outside to the inside during the pre-oxidation stabilization process. Larger particle diameters result in longer diffusion paths for oxygen molecules within the particle, leading to a greater difference in oxidation reaction rates between the outside and inside, thus creating a temperature gradient. When the diameter exceeds a certain value, the external reaction is rapid while the internal reaction lags behind, potentially causing localized overheating or incomplete oxidation. Conversely, smaller particle diameters shorten the oxygen diffusion path, causing surface oxygen molecules to react rapidly with active sites in the asphalt (such as aromatic rings or aliphatic side chains), forming a dense cross-linked layer. This dense layer hinders oxygen diffusion inward, causing premature solidification of the outer layer of the asphalt particle while the interior remains in an incompletely oxidized state. This "shell-core" structural difference can trigger internal stress concentration, leading to asphalt particle cracking or abnormal pore structure. Therefore, it is necessary to determine the optimal diameter range for asphalt particle granulation to ensure a more complete and uniform pre-oxidation reaction.
[0027] During their research, the inventors of this invention discovered that by pulverizing high softening point asphalt into powder asphalt of 80-8000 mesh, and then using wetting agents and binders, the powder asphalt can be directly granulated without the need for additives to lower the softening point of the asphalt or for undergoing a melting process. After the powder asphalt binds and agglomerates, it forms asphalt particles. These asphalt particles have a specific diameter range and porosity, which makes it easy for mass and heat to be transferred between the pores inside and outside the asphalt particles. This ensures sufficient contact with air during the pre-oxidation stabilization process and also avoids the melting and adhesion of the inside and outside of the asphalt particles due to heat accumulation during the pre-oxidation stabilization process.
[0028] The first aspect of this invention provides a method for preparing asphalt particles, the method comprising the following steps: By weight, 100 parts of powdered asphalt are mixed with 5-200 parts of dispersant and 0.1-5 parts of binder and granulated to obtain the asphalt particles.
[0029] Understandably, the weight ratio of powdered asphalt to dispersant must be adjusted within the range of 1:(0.05-2). If the weight ratio of powdered asphalt to dispersant is higher than 1:0.05, the amount of dispersant used is too small, which will cause the asphalt particles to easily agglomerate, with a particle size much larger than 10 mm. At the same time, the powdered asphalt in the asphalt particles will be unevenly distributed, which will easily cause insufficient oxidation of asphalt particles or heat accumulation leading to melting and adhesion during the subsequent pre-oxidation stabilization process. If the weight ratio is lower than 1:2, the amount of dispersant used is too large, which will cause the particle size of the granulated asphalt particles to be much smaller than 0.5 mm, and at the same time, the mechanical strength will be low, making them easy to break during the subsequent pre-oxidation stabilization process.
[0030] Understandably, the weight ratio of powdered asphalt to binder must be adjusted within the range of 1:(0.001-0.05). If the weight ratio of powdered asphalt to binder is higher than 1:0.001, the amount of binder used is excessive. This will cause the powdered asphalt particles to be tightly bonded due to the adhesion effect of excessive binder, forming a dense structure. This can easily lead to insufficient oxidation of asphalt particles or heat accumulation causing melting and adhesion during the subsequent pre-oxidation stabilization process, and the particle size of the granulated asphalt particles will be much larger than 10 mm. If the weight ratio is lower than 1:0.05, the amount of binder used is too small, and the powdered asphalt particles cannot be effectively bonded, resulting in insufficient bonding force between particles. This can easily lead to breakage during the subsequent pre-oxidation stabilization process, and the particle size of the granulated asphalt particles will be much smaller than 0.5 mm.
[0031] According to a preferred embodiment of the present invention, the above-mentioned method for preparing asphalt particles further includes homogenization after mixing.
[0032] The homogenization can be performed in a manner conventional in the art, such as mechanical stirring, vibration, or airflow homogenization.
[0033] According to a preferred embodiment of the present invention, in the above-mentioned method for preparing asphalt particles, 100 parts of powdered asphalt are mixed evenly with 5-99.9 parts of dispersant and 0.1-3 parts of binder by weight, and then granulated to obtain the asphalt particles.
[0034] According to a preferred embodiment of the present invention, in the above-mentioned method for preparing asphalt particles, 100 parts of powdered asphalt, 100-200 parts of dispersant, and 0.1-3 parts of binder are mixed evenly and granulated to obtain the asphalt particles.
[0035] According to a preferred embodiment of the present invention, in the above-mentioned method for preparing asphalt particles, 100 parts of powdered asphalt are mixed evenly with 5-99.9 parts of dispersant and 3-5 parts of binder by weight, and then granulated to obtain the asphalt particles.
[0036] According to a preferred embodiment of the present invention, in the above-mentioned method for preparing asphalt particles, 100 parts by weight of powdered asphalt, 100-200 parts by weight of dispersant, and 3-5 parts by weight of binder are mixed evenly and granulated to obtain the asphalt particles.
[0037] According to a preferred embodiment of the present invention, the softening point of the powdered asphalt may be 250-300℃.
[0038] The method for determining the softening point can be found in GB / T4507-1999, "Determination of Softening Point of Asphalt (Ring and Ball Method)".
[0039] According to a preferred embodiment of the present invention, the particle size of the powdered asphalt can be from 80 mesh to 8000 mesh, preferably 300-3000 mesh. The particle size determination can refer to GB / T 18854 "Test Methods and Procedures for Particle Size Analyzers", and the sieving method used for particle size determination can refer to the American standard "ASTM E11-2013 Standard Specification for Wire Mesh Screens and Test Sieves".
[0040] According to a preferred embodiment of the present invention, the dispersant may be water or ethanol, or a mixture of water and ethanol.
[0041] When the dispersant is a mixture of water and ethanol, the weight ratio of water to ethanol can be any value.
[0042] According to a preferred embodiment of the present invention, the adhesive may be selected from one or more of polyethylene glycol, carboxymethyl cellulose, hydroxymethyl cellulose, and phenolic resin.
[0043] The weight-average molecular weight of the polyethylene glycol can be in the range of 200-20000 g / mol, and it can be a product commercially available from Shanghai Aladdin Biochemical Technology Co., Ltd., or Anhui Wanwei High-Tech Materials Co., Ltd.
[0044] The degree of substitution of the carboxymethyl cellulose can be 0.4-1.4, for example, it can be a product purchased commercially from Shanghai Aladdin Biochemical Technology Co., Ltd., or a product from Ningbo Haisheng Cellulose Derivatives Factory.
[0045] The degree of substitution of the hydroxymethyl cellulose can be 0.4-1.2, for example, it can be a product purchased commercially from Shanghai Aladdin Biochemical Technology Co., Ltd., or a product from Jinzhou Fuqiang Fine Chemical Co., Ltd.
[0046] The viscosity range of the phenolic resin can be 2000-20000 mPa·s. For example, it can be commercially available products with grades 2130 and 6216 from Wuxi Xinyehao Chemical Co., Ltd., or products from Henan Yixiang New Materials Co., Ltd.
[0047] According to a preferred embodiment of the present invention, the powdered asphalt can be obtained by first crushing and sieving the high softening point asphalt.
[0048] The softening point of the high softening point asphalt can be 250-300℃. In this field, a softening point above 90℃ is considered a high softening point.
[0049] The first crushing can be carried out by mechanical grinding or air jet milling.
[0050] The screening can be carried out by vibrating screening or airflow screening.
[0051] According to a preferred embodiment of the present invention, the granulation can be carried out by a disc pelletizer, a drum pelletizer, an extrusion pelletizer, or an extrusion-shot blasting pelletizer.
[0052] A second aspect of the present invention provides asphalt particles prepared by the above-described preparation method.
[0053] The average diameter of the asphalt particles can be 0.5-10 mm, preferably 1-5 mm.
[0054] It is understood that the average diameter of the asphalt particles must be adjusted within the range of 0.5-10mm. If the average diameter of the asphalt particles is higher than 10mm, it will cause local heat accumulation and overheating of the asphalt particles during the pre-oxidation stabilization process, making them prone to melting and adhesion, or causing incomplete oxidation reaction of the asphalt particles. If the average diameter of the asphalt particles is lower than 0.5mm, it will easily cause the asphalt particles to crack or have abnormal pore structure.
[0055] The bulk density of the asphalt particles can be 0.3-0.8 g / cm³. 3 The preferred concentration is 0.5-0.7 g / cm³. 3 .
[0056] The porosity of the asphalt particles can be 5-15%, preferably 6-13%.
[0057] A third aspect of the present invention provides asphalt-based oxidized particles, which are obtained by pre-oxidizing and stabilizing the aforementioned asphalt particles.
[0058] The oxygen content of the asphalt-based oxidized particles is 12-35 wt.%, preferably 14-35 wt.%.
[0059] It is understood that the oxygen content of the asphalt-based oxide particles must be adjusted within the range of 12-35 wt.%. If the oxygen content of the asphalt-based oxide particles is higher than 35 wt.%, the particles will easily decompose into gases (such as CO and CO2) during high-temperature carbonization, resulting in a large loss of carbon atoms. If the oxygen content is lower than 12 wt.%, the oxidation degree of the particles will be low, making it impossible to form a stable cross-linked structure on the surface and inside. The particles will easily melt and stick together, leading to graphitization during the subsequent carbonization process of hard carbon materials. At the same time, during the activation process of activated carbon materials, the contact between the asphalt-based precursor and the activator is reduced, resulting in a significant decrease in the specific surface area of the asphalt-based precursor.
[0060] The pre-oxidation stabilization conditions may be: an oxidizing gas atmosphere; starting at room temperature, increasing the temperature to the pre-oxidation stabilization temperature of 280-350℃ at a rate of 0.2-5℃ / min, and holding for 0.5-6 hours.
[0061] According to a preferred embodiment of the present invention, the oxidizing gas atmosphere may be O2, O3, SO3, NO2 or air.
[0062] A fourth aspect of the present invention provides a hard carbon material, which is obtained by carbonizing the above-mentioned pitch-based oxide particles.
[0063] The carbonization conditions may be as follows: an inert gas atmosphere; starting at room temperature, heating to the carbonization temperature of 900-1500℃ at a rate of 2-10℃ / min, holding at that temperature for 1-3 hours, then cooling to 800-1200℃ at a rate of 2-5℃ / min, and then naturally cooling to room temperature to obtain the hard carbon material.
[0064] Wherein, the carbon interlayer spacing d of the hard carbon material 002The value can be 0.37-0.41 nm and can be determined by powder X-ray diffraction. The interlayer spacing d of the carbon layers is... 002 The value indicates that hard carbon materials have a large interlayer spacing, which enables them to store more sodium ions.
[0065] The sodium storage capacity of the hard carbon material can be 260-400 mAh / g, which can be determined by the method in GB / T 43114-2023 Hard Carbon. The sodium storage capacity characterization shows that the hard carbon material can significantly improve the energy density of the battery made from it.
[0066] Wherein, the width L of the microcrystals of the hard carbon material along the a-axis direction a The thickness L along the c-axis can be 2.325-2.443 nm. c It can be 1.101-1.204nm. L a L c L can be determined by powder X-ray diffraction. a L c Characterization results indicate that hard carbon materials possess a small-sized microcrystalline structure.
[0067] According to a preferred embodiment of the present invention, the carbonization process may further include a second crushing of the asphalt-based oxide particles.
[0068] The second crushing can be carried out by mechanical grinding or air jet milling.
[0069] The average diameter of the second crushed asphalt-based oxidized particles can be 0.5-5 μm.
[0070] The fifth aspect of this invention provides an application of the above-mentioned hard carbon material in the preparation of battery anode materials.
[0071] The sixth aspect of the present invention provides an activated carbon material, which is obtained by activating the above-mentioned pitch-based oxide particles.
[0072] The activation conditions may be as follows: an inert gas atmosphere; starting at room temperature, heating to the activation temperature of 700-1100℃ at a rate of 8-12℃ / min, and then introducing an activating agent at this temperature for 1-20 hours, followed by natural cooling to room temperature.
[0073] The activator may be water vapor, carbon dioxide, or a mixture of both.
[0074] When the activator is water vapor, the activation time is 1-3 hours and the activator-to-carbon ratio is (1-4):1.
[0075] When the activator is carbon dioxide, the activation time is 2-8 hours and the activator-to-carbon ratio is (2-20):1.
[0076] When the activator is a mixture of carbon dioxide and water vapor, the activation time is 1-4 hours and the activator-to-carbon ratio is (1-6):1; the mass ratio of carbon dioxide to water vapor in the mixture is (20-40):(80-60).
[0077] The average diameter of the activated carbon material can be 0.2-8 mm, preferably 1-5 mm.
[0078] The specific surface area of the activated carbon material can be 800-2900 m². 2 / g, preferably 1500-2000m 2 / g.
[0079] According to a preferred embodiment of the present invention, the inert gas atmosphere may be one or more of helium, neon, argon, krypton, and xenon.
[0080] The seventh aspect of the present invention provides an application of the above-mentioned activated carbon material in the fields of blood purification, industrial wastewater treatment, supercapacitors, silicon-carbon anode carriers, or gas separation.
[0081] According to a particularly preferred embodiment of the present invention, the method for preparing the above-mentioned hard carbon material includes the following steps: S1. By weight, 100 parts of powdered asphalt with a particle size of 300-8000 mesh are mixed with 10-20 parts of ethanol and 3-5 parts of polyethylene glycol with a molecular weight of 10000. The mixture is then placed in a disc granulator for granulation to obtain asphalt particles. S2. The asphalt particles obtained in step S1 are heated to the pre-oxidation stabilization temperature of 320-350℃ at a rate of 3-5℃ / min in an air atmosphere with room temperature as the initial temperature and the residence time is 3-6 hours to obtain asphalt-based oxidized particles. S3. The asphalt-based oxide particles obtained in step S2 are crushed into particles with an average diameter of 0.5-2 μm. Under an argon atmosphere, the initial temperature is room temperature, and the temperature is increased to the carbonization temperature of 900-1300℃ at a rate of 3-10℃ / min. The temperature is held for 2-3 hours, and then the temperature is decreased to 800-1200℃ at a rate of 2-5℃ / min. The temperature is then allowed to cool naturally to room temperature to obtain hard carbon material.
[0082] According to a particularly preferred embodiment of the present invention, the preparation method of the above-mentioned activated carbon material includes the following steps: S1. By weight, 100 parts of powdered asphalt with a particle size of 300-8000 mesh are mixed with 10-20 parts of ethanol and 3-5 parts of polyethylene glycol with a molecular weight of 10000. The mixture is then placed in an extrusion granulator to granulate the mixture and obtain asphalt particles. S2. The asphalt particles obtained in step S1 are heated to the pre-oxidation stabilization temperature of 320-350℃ at a rate of 3-5℃ / min in an air atmosphere with room temperature as the initial temperature and the residence time is 3-6 hours to obtain asphalt-based oxidized particles. S3. Under a helium atmosphere, with room temperature as the initial temperature, the pitch-based oxide particles obtained in step S2 are heated to the activation temperature of 800-1100℃ at a rate of 8-10℃ / min. When the activation temperature is reached, water vapor is introduced for activation for 1-3 hours, with an agent-to-carbon ratio of 2-4. After the reaction is completed, the mixture is naturally cooled to room temperature to obtain activated carbon material.
[0083] The present invention will be described in detail below through examples. In the following examples, the bulk density of asphalt particles was determined using the method specified in GB / T 21354-2008 General Method for Determination of Tap Density of Powder Products; The specific surface area, average pore size, and pore volume of activated carbon materials were determined using the method specified in GB / T 7702.20-2008 "Test Methods for Coal-based Granular Activated Carbon - Determination of Pore Volume and Specific Surface Area". The average diameter of activated carbon materials was determined using the laser light scattering method. Microcrystalline structure parameters of hard carbon materials (002): interplanar spacing (d) 002 ), the average width of graphite crystals along the a-axis (L) a ), the thickness of the deposit along the c-axis (L) c The determination was performed using powder X-ray diffraction. Sodium storage capacity was determined using the method specified in GB / T 43114-2023 Hard Carbon.
[0084] In the following examples, polyethylene glycol (weight average molecular weight 200-20000 g / mol) is a product of Shanghai Aladdin Biochemical Technology Co., Ltd. with the brand name P103728; Carboxymethyl cellulose (degree of substitution 0.4-1.4) and hydroxymethyl cellulose (degree of substitution 0.4-1.2) are both commercially available products of Shanghai Aladdin Biochemical Technology Co., Ltd. Phenolic resins (viscosity range 2000-20000 mPa·s) are commercially available products from Wuxi Xinyehao Chemical Co., Ltd., with brand names 2130 and 6216 respectively. The commercially available asphalt granules with an average diameter of 2mm are the RefineU Black Qi-PE280 product from Liaoning Aoyida New Material Co., Ltd., with a softening point of 275-285℃.
[0085] Preparation Example 1 By weight, asphalt with a softening point of 250℃ is pulverized to obtain asphalt powder with a particle size of 80 mesh. Five parts of polyethylene glycol with a weight-average molecular weight of 200 g / mol and 20 parts of ethanol are added to 100 parts of the above asphalt powder and mixed thoroughly. The resulting mixture is then placed into a disc granulator for granulation to obtain asphalt particles A.
[0086] Preparation Example 2 By weight, asphalt with a softening point of 280℃ was pulverized to obtain asphalt powder with a particle size of 8000 mesh. 0.1 parts of carboxymethyl cellulose with a degree of substitution of 1 and 10 parts of water were added to 100 parts of the above asphalt powder and mixed thoroughly. The resulting mixture was then placed into a rotary drum granulator for granulation to obtain asphalt particles B.
[0087] Preparation Example 3 By weight, asphalt with a softening point of 300℃ is pulverized to obtain asphalt powder with a particle size of 3000 mesh. 3 parts of hydroxymethyl cellulose with a degree of substitution of 0.9 and 20 parts of water are added to 100 parts of the above asphalt powder and mixed thoroughly. The resulting mixture is then placed into a disc granulator for granulation to obtain asphalt particles C.
[0088] Preparation Example 4 By weight, asphalt with a softening point of 250℃ is pulverized to obtain asphalt powder with a particle size of 80 mesh. Three parts of polyethylene glycol with a molecular weight of 10000 g / mol and ten parts of ethanol are added to 100 parts of the above asphalt powder and mixed thoroughly. The resulting mixture is then fed into a rotary drum granulator for granulation to obtain asphalt particles D.
[0089] Preparation Example 5 By weight, asphalt with a softening point of 280℃ was pulverized to obtain asphalt powder with a particle size of 200 mesh. 0.1 parts of phenolic resin with a viscosity of 2000 mPa·s and 5 parts of ethanol were added to 100 parts of the above asphalt powder and mixed thoroughly. The resulting mixture was then fed into an extrusion granulator for granulation to obtain asphalt particles E.
[0090] Preparation Example 6 By weight, asphalt with a softening point of 250℃ was pulverized to obtain asphalt powder with a particle size of 80 mesh. Three parts of polyethylene glycol with a weight-average molecular weight of 20,000 g / mol and 200 parts of ethanol were added to 100 parts of the above asphalt powder and mixed thoroughly. The resulting mixture was then placed into an extrusion-shot blasting granulator for granulation to obtain asphalt particles F.
[0091] Example 1 The asphalt particles A obtained in Preparation Example 1 were heated to the pre-oxidation stabilization temperature of 350°C at a rate of 0.2°C / min under an air atmosphere, with room temperature as the initial temperature, and the residence time was 6 hours to obtain asphalt-based oxidized particles A1.
[0092] Example 2 The asphalt particles B obtained in Preparation Example 2 were heated to the pre-oxidation stabilization temperature of 350°C at a rate of 2°C / min under an air atmosphere, with room temperature as the initial temperature and a residence time of 0.5 hours, to obtain asphalt-based oxidized particles B1.
[0093] Example 3 The asphalt particles C obtained in Preparation Example 3 were heated to a pre-oxidation stabilization temperature of 280°C at a rate of 5°C / min under air atmosphere, starting at room temperature, and held for 3 hours to obtain asphalt-based oxidized particles C1. The obtained asphalt-based oxidized particles C1 were photographed. Figure 1 As can be seen from the photos, the asphalt-based oxidized particles C1 obtained by the granulation and pre-oxidation method of this invention are spherical particles with relatively complete particle morphology.
[0094] Example 4 The asphalt particles D obtained in Preparation Example 4 were heated to the pre-oxidation stabilization temperature of 350°C at a rate of 3°C / min under an air atmosphere, with room temperature as the initial temperature and a residence time of 3.5 hours, to obtain asphalt-based oxidized particles D1.
[0095] Example 5 The asphalt particles E obtained in Preparation Example 5 were heated to the pre-oxidation stabilization temperature of 320°C at a rate of 3°C / min under an air atmosphere, with room temperature as the initial temperature and a residence time of 4.5 hours, to obtain asphalt-based oxidized particles E1.
[0096] Example 6 The asphalt particles F prepared in Preparation Example 6 were heated to the pre-oxidation stabilization temperature of 350°C at a rate of 1.5°C / min under an air atmosphere, with room temperature as the initial temperature, and the residence time was 1.5 hours to obtain asphalt-based oxidized particles F1.
[0097] Table 1
[0098] The average diameter and bulk density of asphalt particles AF, and the oxygen content of asphalt-based oxidized particles A1-F1 were measured, and the results are shown in Table 1. As can be seen from the results of preparation examples 1-6 and embodiments 1-6 recorded in Table 1, the asphalt particles prepared using the granulation method of the present invention can ensure sufficient contact with air during the pre-oxidation stabilization process, and can also minimize or avoid melting and adhesion of the internal and external parts of the asphalt particles due to heat accumulation during the pre-oxidation stabilization process.
[0099] Application Example 1 Pitch-based oxide particles A1 were crushed into particles with an average diameter of 5 μm. Under an argon atmosphere, the initial temperature was increased to the carbonization temperature of 1300℃ at a rate of 3℃ / min, and held for 2 hours. Then the temperature was decreased to 1000℃ at a rate of 3℃ / min, and then naturally cooled to room temperature to obtain hard carbon material A2.
[0100] Application Example 2 Pitch-based oxide particles B1 were crushed into particles with an average diameter of 0.5 μm. Under a helium atmosphere, the initial temperature was increased to the carbonization temperature of 1500℃ at a rate of 2℃ / min, and held for 3 hours. Then the temperature was decreased to 1200℃ at a rate of 5℃ / min, and then naturally cooled to room temperature to obtain hard carbon material B2.
[0101] Application Example 3 Pitch-based oxide particles C1 were crushed into particles with an average diameter of 2 μm. Under an argon atmosphere, the initial temperature was increased to the carbonization temperature of 900°C at a rate of 10°C / min, and held for 2 hours. Then, the temperature was decreased to 800°C at a rate of 2°C / min, and then allowed to cool naturally to room temperature to obtain hard carbon material C2. Figure 2 This is the XRD pattern of hard carbon material C2.
[0102] Application Example 4 Pitch-based oxide particles D1 were crushed to form particles with an average diameter of 3.4 μm. Under a helium atmosphere, the initial temperature was increased to the carbonization temperature of 1000℃ at a rate of 5℃ / min, and held for 2 hours. Then, the temperature was decreased to 800℃ at a rate of 2.5℃ / min, and then allowed to cool naturally to room temperature to obtain hard carbon material D2.
[0103] Application Example 5 Pitch-based oxide particles E1 were crushed into particles with an average diameter of 4 μm. Under an argon atmosphere, the initial temperature was increased to the carbonization temperature of 1400℃ at a rate of 8℃ / min, and held for 1 hour. Then, the temperature was decreased to 1000℃ at a rate of 5℃ / min, and then allowed to cool naturally to room temperature to obtain hard carbon material E2.
[0104] Application Example 6 Pitch-based oxide particles F1 were crushed into particles with an average diameter of 1 μm. Under an argon atmosphere, the initial temperature was increased to the carbonization temperature of 1200℃ at a rate of 9℃ / min, and held for 2 hours. Then, the temperature was decreased to 900℃ at a rate of 4℃ / min, and then naturally cooled to room temperature to obtain hard carbon material F2.
[0105] Table 2
[0106] The microcrystalline structure parameters and sodium storage capacity of the hard carbon materials in Application Examples 1-6 were measured, and the results are shown in Table 2. As can be seen from the results of Application Examples 1-6 recorded in Table 2, the pitch-based oxide particles prepared using the granulation and pre-oxidation stabilization method of the present invention, when applied to the preparation of hard carbon materials, result in hard carbon materials with high sodium storage capacity.
[0107] Application Example 7 Under an argon atmosphere, with room temperature as the initial temperature, asphalt-based oxide particles A1 were heated to the activation temperature of 900℃ at a rate of 10℃ / min. Water vapor was then introduced at 900℃ for 1 hour to activate the material, with an agent-to-carbon ratio of 4:1. After the reaction, the material was naturally cooled to room temperature to obtain activated carbon material A3.
[0108] Application Example 8 Under a helium atmosphere, with room temperature as the initial temperature, pitch-based oxide particles B1 were heated to the activation temperature of 700°C at a rate of 8°C / min. Carbon dioxide was then introduced at 700°C for 8 hours of activation, with a catalyst-to-carbon ratio of 20:1. After the reaction was completed, the mixture was allowed to cool naturally to room temperature to obtain activated carbon material B3.
[0109] Application Example 9 Under an argon atmosphere, with room temperature as the initial temperature, asphalt-based oxide particles C1 were heated to the activation temperature of 900℃ at a rate of 9℃ / min. Water vapor was then introduced at 900℃ for 3 hours of activation, with a catalyst-to-carbon ratio of 1:1. After the reaction was completed, the mixture was allowed to cool naturally to room temperature to obtain activated carbon material C3. Figure 3 The nitrogen adsorption isotherm diagram of activated carbon material C is shown below. Figure 3 It can be seen that the activated carbon material C3 prepared by the granulation, pre-oxidation stabilization, and activation methods of this invention has strong adsorption performance, and the maximum nitrogen adsorption capacity that can be achieved at a relative pressure P / P0 of 1 is 475 cm³. 3 ·g -1 STP.
[0110] Application Example 10 Under an argon atmosphere, with room temperature as the initial temperature, the pitch-based oxide particles D1 were heated to the activation temperature of 1100℃ at a rate of 12℃ / min. At 1100℃, a mixture of carbon dioxide and water vapor (mass ratio of 40:60) was introduced for 1 hour for activation, with an agent-to-carbon ratio of 1:1. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain activated carbon material D3.
[0111] Application Example 11 Under a helium atmosphere, with room temperature as the initial temperature, the asphalt-based oxide particles E1 were heated to the activation temperature of 900℃ at a rate of 11℃ / min. At 900℃, a mixture of carbon dioxide and water vapor (mass ratio of 20:80) was introduced for activation for 4 hours, with an agent-to-carbon ratio of 6:1. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain activated carbon material E3.
[0112] Application Example 12 Under an argon atmosphere, with room temperature as the initial temperature, asphalt-based oxide particles F1 were heated to the activation temperature of 800℃ at a rate of 8℃ / min. Carbon dioxide was then introduced at 800℃ for 2 hours of activation, with a catalyst-to-carbon ratio of 2:1. After the reaction was completed, the mixture was allowed to cool naturally to room temperature to obtain activated carbon material F3.
[0113] Table 3
[0114] The BET specific surface area, pore volume, average pore size, and average diameter of the activated carbon materials in Application Examples 7-12 were measured, and the results are shown in Table 3. As can be seen from the results of Application Examples 7-12 recorded in Table 3, the pitch-based oxide particles prepared using the granulation and pre-oxidation stabilization method of the present invention, when applied to the preparation of activated carbon materials, result in activated carbon materials with a high BET specific surface area. Figure 3 It can be seen that the activated carbon material C prepared by the granulation, pre-oxidation stabilization, and activation methods of this invention has strong adsorption performance, and the maximum nitrogen adsorption capacity achievable at a relative pressure P / P0 of 1 is 475 cm³. 3 ·g -1 STP.
[0115] Application Comparative Example 1 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the pulverization and carbonization conditions were the same as those for Application Example 2. The asphalt particles were not produced using the granulation process of this invention, but were instead made directly from commercially available asphalt particles with an average diameter of 2 mm. These commercially available asphalt particles were prepared according to the naphthalene-added melt granulation method described in CN113912059B. The resulting asphalt-based oxide particles had an oxygen content of 4.7%, and significant melting and adhesion of the asphalt-based oxide particles was observed. The resulting hard carbon material G had a carbon interlayer spacing of 0.355 nm and a sodium storage capacity of 95 mAh / g.
[0116] Application Comparative Example 2 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the crushing and carbonization conditions were the same as those for Application Example 2. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of ethanol used was 250 parts. The average diameter of the obtained asphalt particles was 0.24 mm, the porosity was 24%, and the oxygen content of the obtained asphalt-based oxide particles was 51%. It was observed that the asphalt-based oxide particles were severely broken during the subsequent carbonization process. The carbon interlayer spacing of the obtained hard carbon material H was 0.351 nm, and the sodium storage capacity was 83 mAh / g.
[0117] Application Comparative Example 3 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the crushing and carbonization conditions were the same as those for Application Example 2. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of ethanol used was 2 parts. The average diameter of the obtained asphalt particles was 15 mm, the porosity was 2%, and the oxygen content of the obtained asphalt-based oxide particles was 6%. It was observed that the degree of melting and adhesion of the asphalt-based oxide particles was relatively serious. The carbon interlayer spacing of the obtained hard carbon material I was 0.352 nm, and the sodium storage capacity was 86 mAh / g.
[0118] Application Comparative Example 4 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the crushing and carbonization conditions were the same as those for Application Example 2. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of polyethylene glycol was 10 parts. The average diameter of the obtained asphalt particles was 20 mm, the porosity was 1%, and the oxygen content of the obtained asphalt-based oxide particles was 4%. It was observed that the degree of melting and adhesion of the asphalt-based oxide particles was relatively serious. The carbon interlayer spacing of the obtained hard carbon material J was 0.357 nm, and the sodium storage capacity was 98 mAh / g.
[0119] Application Comparative Example 5 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the crushing and carbonization conditions were the same as those for Application Example 2. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of polyethylene glycol was 0.05 parts. The average diameter of the obtained asphalt particles was 0.16 mm, the porosity was 21%, and the oxygen content of the obtained asphalt-based oxide particles was 59%. It was observed that the asphalt-based oxide particles were severely broken during the subsequent carbonization process. The carbon interlayer spacing of the obtained hard carbon material K was 0.353 nm, and the sodium storage capacity was 90 mAh / g.
[0120] By comparing the results of Comparative Example 1 with those of Example 1 and Example 2, it can be seen that when the granulation process and pre-oxidation stabilization process of the present invention are not used, the asphalt-based oxide particles prepared by the commercially available asphalt particles prepared by melt granulation have a more severe degree of melting and adhesion, and the oxygen content is too low. They are prone to graphitization during carbonization, resulting in a significant reduction in the sodium storage capacity of the prepared hard carbon material. Comparing Comparative Example 2 with the results of Preparation Example 1, Example 1, and Application Example 2, it can be seen that when the weight ratio of powdered asphalt to dispersant in the granulation process is less than 1:2, the resulting asphalt particles have too small a particle size and too high a porosity, leading to excessively high oxygen content in the asphalt-based oxidized particles. This results in severe breakage of the asphalt-based oxidized particles during subsequent carbonization, significantly reducing the sodium storage capacity of the hard carbon material. Comparing Comparative Example 3 with the results of Preparation Example 1, Example 1, and Application Example 2, it can be seen that when the weight ratio of powdered asphalt to dispersant in the granulation process is greater than 1:0.05, the resulting asphalt particles have too large a particle size and too low a porosity, leading to excessively low oxygen content in the asphalt-based oxidized particles. This results in insufficient oxidation of the asphalt-based oxidized particles, which are prone to melting and agglomeration due to heat accumulation during pre-oxidation, significantly reducing the sodium storage capacity of the hard carbon material after carbonization. Comparing Comparative Example 4 with the results of Preparation Example 1, Example 1, and Application Example 2, it can be seen that when the weight ratio of powdered asphalt to binder in the granulation process is less than 1:0.05, the resulting asphalt particles have excessively large particle size and low porosity, leading to excessively low oxygen content in the asphalt-based oxidized particles. This results in insufficient oxidation of the asphalt-based oxidized particles, which are prone to melting and agglomeration due to heat accumulation during pre-oxidation, significantly reducing the sodium storage capacity of the hard carbon material obtained after carbonization. Comparing Comparative Example 5 with the results of Preparation Example 1, Example 1, and Application Example 2, it can be seen that when the weight ratio of powdered asphalt to binder in the granulation process is greater than 1:0.001, the resulting asphalt particles have excessively small particle size and high porosity, leading to excessively high oxygen content in the asphalt-based oxidized particles. This results in severe breakage of the asphalt-based oxidized particles during subsequent carbonization, significantly reducing the sodium storage capacity of the hard carbon material obtained.
[0121] Application Comparative Example 6 The pre-oxidation conditions for this comparative application were the same as in Example 1, and the activation conditions were the same as in Application Example 7. The asphalt particles were not produced using the granulation process of this invention, but rather commercially available asphalt particles with an average diameter of 2 mm were used directly as raw material. These commercially available asphalt particles were prepared according to the naphthalene-added melt granulation method described in CN113912059B. The oxygen content of the obtained asphalt-based oxidized particles was 4.3%, and significant melting and adhesion of the asphalt-based oxidized particles was observed. The BET specific surface area of the obtained activated carbon material G1 was 268 m². 2 / g.
[0122] Application Comparative Example 7 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the activation conditions were the same as those for Application Example 7. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of ethanol used was 240 parts. The average diameter of the obtained asphalt particles was 0.21 mm, the porosity was 25%, and the oxygen content of the obtained asphalt-based oxide particles was 55%. It was observed that the asphalt-based oxide particles were severely broken during the subsequent carbonization process. The BET specific surface area of the obtained activated carbon material H1 was 131 m². 2 / g.
[0123] Application Comparative Example 8 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the activation conditions were the same as those for Application Example 7. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of ethanol used was 1 part. The average diameter of the obtained asphalt particles was 17 mm, the porosity was 2%, and the oxygen content of the obtained asphalt-based oxide particles was 4.5%. It was observed that the degree of melting and adhesion of the asphalt-based oxide particles was relatively serious. The BET specific surface area of the obtained activated carbon material I1 was 78 m². 2 / g.
[0124] Application Comparison Example 9 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the activation conditions were the same as those for Application Example 7. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of polyethylene glycol was 0.03 parts. The average diameter of the obtained asphalt particles was 0.11 mm, the porosity was 30%, and the oxygen content of the obtained asphalt-based oxidized particles was 63%. It was observed that the asphalt-based oxidized particles were severely broken during the subsequent carbonization process. The BET specific surface area of the obtained activated carbon material J1 was 157 m². 2 / g.
[0125] Application Comparison Example 10 The pre-oxidation conditions for this comparative application were the same as those for Example 1, and the activation conditions were the same as those for Application Example 7. The preparation conditions for the asphalt particles were the same as those for Preparation Example 1, except that the amount of polyethylene glycol was 8 parts. The average diameter of the obtained asphalt particles was 16.3 mm, the porosity was 2.5%, and the oxygen content of the obtained asphalt-based oxide particles was 5.1%. It was observed that the degree of melting and adhesion of the asphalt-based oxide particles was relatively serious. The BET specific surface area of the obtained activated carbon material K1 was 83 m². 2 / g.
[0126] By comparing the results of Comparative Example 6 with those of Example 1 and Example 7, it can be seen that when the granulation process and pre-oxidation stabilization process of the present invention are not used, the asphalt-based oxide particles prepared by the melt granulation method are more prone to melting and adhesion, and the oxygen content is too low. The contact between the asphalt-based oxide particles and the activator is reduced, resulting in a significant decrease in the specific surface area of the prepared activated carbon material. Comparing the results of Comparative Example 7 with those of Preparation Example 1, Example 1, and Application Example 7, it can be seen that when the weight ratio of powdered asphalt to dispersant in the granulation process is less than 1:2, the resulting asphalt particles have too small a particle size and too high porosity, leading to excessively high oxygen content in the asphalt-based oxide particles. This results in severe breakage of the asphalt-based oxide particles during subsequent carbonization, causing a significant decrease in the specific surface area of the resulting activated carbon material. Comparing the results of Comparative Example 8 with those of Preparation Example 1, Example 1, and Application Example 7, it can be seen that when the weight ratio of powdered asphalt to dispersant in the granulation process is greater than 1:0.05, the resulting asphalt particles have too large a particle size and too low porosity, leading to excessively low oxygen content in the asphalt-based oxide particles. This results in insufficient oxidation of the asphalt-based oxide particles, making them prone to melting and agglomeration due to heat accumulation during pre-oxidation. This reduces the contact between the asphalt-based oxide particles and the activator, resulting in a significant decrease in the specific surface area of the resulting activated carbon material. Comparing the results of Comparative Example 9 with those of Preparation Example 1, Example 1, and Application Example 7, it can be seen that when the weight ratio of powdered asphalt to binder in the granulation process is less than 1:0.05, the resulting asphalt particles have excessively large particle size and low porosity, leading to excessively low oxygen content in the asphalt-based oxidized particles. This results in insufficient oxidation of the asphalt-based oxidized particles, which are prone to melting and agglomeration due to heat accumulation during pre-oxidation. Reduced contact between the asphalt-based oxidized particles and the activator further reduces the specific surface area of the resulting activated carbon material. Conversely, comparing the results of Comparative Example 10 with those of Preparation Example 1, Example 1, and Application Example 7, it can be seen that when the weight ratio of powdered asphalt to binder in the granulation process is greater than 1:0.001, the resulting asphalt particles have excessively small particle size and high porosity, leading to excessively high oxygen content in the asphalt-based oxidized particles. This results in severe breakage of the asphalt-based oxidized particles during subsequent carbonization, further reducing the specific surface area of the resulting activated carbon material.
[0127] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A type of asphalt-based oxidized particle, characterized in that, The asphalt-based oxidized particles are obtained by pre-oxidizing and stabilizing asphalt particles; The method for preparing asphalt particles includes the following steps: By weight, 100 parts of powdered asphalt are mixed with 5-200 parts of dispersant and 0.1-5 parts of binder and granulated to obtain the asphalt particles; The softening point of the powdered asphalt is 250-300℃; The average diameter of the asphalt particles is 0.5-10 mm; The pre-oxidation stabilization conditions are as follows: oxidizing gas atmosphere; starting from room temperature, heating to the pre-oxidation stabilization temperature of 280-350℃ at a rate of 0.2-5℃ / min, and residence time of 0.5-6 hours.
2. The asphalt-based oxidized particles according to claim 1, wherein, The particle size of the powdered asphalt is from 80 mesh to 8000 mesh; And / or, the dispersant is water or ethanol, or a mixture of water and ethanol; And / or, the adhesive is selected from one or more of polyethylene glycol, carboxymethyl cellulose, hydroxymethyl cellulose, and phenolic resin; And / or, the bulk density of the asphalt particles is 0.3-0.8 g / cm³. 3 ; And / or, the porosity of the asphalt particles is 5%-15%.
3. A hard carbon material, characterized in that, The hard carbon material is obtained by carbonizing the asphalt-based oxide particles as described in claim 1 or 2, wherein the oxygen content of the asphalt-based oxide particles is 12-35 wt.%; the carbonization conditions are: an inert gas atmosphere; starting at room temperature, heating to the carbonization temperature of 900-1500℃ at a rate of 2-10℃ / min, holding at that temperature for 1-3 hours, then cooling to 800-1200℃ at a rate of 2-5℃ / min, and then naturally cooling to room temperature to obtain the hard carbon material.
4. The hard carbon material according to claim 3, wherein, The carbon interlayer spacing d002 value of the hard carbon material is 0.37-0.41 nm; And / or, the sodium storage capacity of the hard carbon material is 260-400 mAh / g.
5. The application of the hard carbon material according to claim 3 or 4 in the preparation of battery anode materials.
6. An activated carbon material, characterized in that, The activated carbon material is obtained by activating the asphalt-based oxide particles as described in claim 3 or 4, wherein the oxygen content of the asphalt-based oxide particles is 12-35 wt.%; the activation conditions are: inert gas atmosphere; starting from room temperature, heating to the activation temperature of 700-1100℃ at a rate of 8-12℃ / min, and activating with an activating agent at this temperature for 1-20 hours, and then naturally cooling to room temperature after activation; The activator is water vapor, carbon dioxide, or a mixture of both; When the activator is water vapor, the activation time is 1-3 hours, and the agent-to-carbon ratio is (1-4):1; When the activator is carbon dioxide, the activation time is 2-8 hours, and the activator-to-carbon ratio is (2-20):
1. When the activator is a mixture of carbon dioxide and water vapor, the activation time is 1-4 hours and the activator-to-carbon ratio is (1-6):1; the mass ratio of carbon dioxide to water vapor in the mixture is (20-40):(80-60).
7. The activated carbon material according to claim 6, wherein, The average diameter of the activated carbon material is 0.2-8 mm; And / or, the BET specific surface area of the activated carbon material is 800-2900 m². 2 / g; And / or, the pore volume of the activated carbon material is 0.40-1.36 cm³. 3 / g; And / or, the average pore size of the activated carbon material is 1.83-2.35 nm.
8. The application of the activated carbon material according to claim 6 or 7 in the fields of industrial wastewater treatment, supercapacitors, silicon-carbon anode carriers, or gas separation.
Citation Information
Patent Citations
Melt granulation method of water-cooling method asphalt-based spherical activated carbon
CN108395899A
A pitch-based spherical activated carbon, its preparation method and application
CN113912059B
Process for preparing spherical activated carbon granule
KR100797141B1